2012
DOI: 10.1590/s2237-93632012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of 175 patients with Crohn's disease submitted to biological therapy

Abstract: Introduction: There is currently an increasing use of biological agents in the management of Crohn's disease (CD). There is lack of data regarding the epidemiological profile of patients on infliximab (IFX) and adalimumab (ADA) for CD in Brazil. Objective: To identify the epidemiological characteristics of patients with CD who underwent biological therapy. Method: Retrospective multicenter study, with CD patients on biological therapy. Analyzed variables: gender, age at treatment initiation, Montreal classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
4
0
4
Order By: Relevance
“…[50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD. [24] The larger case-series in LAC Countries are from 1946 to date are from Argentina [14,51,52], Barbados [13], Brazil [14,[53][54][55][56][57][58][59][60][61][62][63][64][65], Chile [66][67][68], Cuba [69], Peru [70,71], Puerto Rico [72][73][74][75] and Uruguay. [76][77][78] Most CD localizations were ileal-colonic and CD behavior was mostly inflammatory, followed by penetrant or stenotic.…”
Section: Discussionmentioning
confidence: 99%
“…[50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD. [24] The larger case-series in LAC Countries are from 1946 to date are from Argentina [14,51,52], Barbados [13], Brazil [14,[53][54][55][56][57][58][59][60][61][62][63][64][65], Chile [66][67][68], Cuba [69], Peru [70,71], Puerto Rico [72][73][74][75] and Uruguay. [76][77][78] Most CD localizations were ileal-colonic and CD behavior was mostly inflammatory, followed by penetrant or stenotic.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, alguns relatos sugerem o impacto da doença na vida profissional: um dos pacientes referiu se sentir mal com as faltas e as saídas antecipadas, por saber que seu chefe "não gosta"; uma mulher alegou ter sofrido um acidente de trânsito, gerado pelo estresse ao ter perdido o emprego; outro paciente se aposentou por invalidez, devido à colocação de bolsa coletora; e dois outros referiram ter se afastado, em decorrência da ocupação que tinham, uma por trabalhar como manipuladora de alimentos e os sintomas gastrointestinais colocarem em risco a segurança do alimento; e o outro por ser pescador, já que os sintomas lhe impossibilitavam de permanecer em alto-mar. Para Hardt et al 15 , o impacto no trabalho também se dá pelo distúrbio ocorrer principalmente entre adolescentes e adultos jovens, grupo etário de grande produtividade.…”
Section: Aspectos Psicossociaisunclassified
“…Enquanto a DC é um processo inflamatório transmural que pode afetar todo o trato gastrointestinal de maneira descontínua. Ambas têm como característica a alternância de episódios de atividade e remissão, e extensão variáveis 3,13,15 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Crohn's disease (CD) is in itself a major challenge for those treating inflammatory bowel diseases. Patients presenting with the fistulizing form, particularly perianal fistulas, create even more of a challenge, as there is great difficulty in controlling the disease even with the therapeutic advances for long-term treatment made in recent years 1 .…”
Section: B Introductionmentioning
confidence: 99%